2012
DOI: 10.3109/15563650.2012.748195
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen/diphenhydramine overdose in profound hypothermia

Abstract: Profound hypothermia may be protective of hepatic injury in acetaminophen overdose. Delayed absorption from the coingestant, diphenhydramine, may also have played a role. IV NAC was given in a standard dose without apparent toxicity in the setting of profound hypothermia. Lastly, IV NAC, in standard dosing, appeared to be effective in preventing hepatotoxicity during rewarming in a patient with a potentially hepatotoxic concentration of acetaminophen with a coingestion of the anticholinergic agent, diphenhydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The effect of APAP on non-febrile temperature regulation has been investigated previously in mice ( Ayoub et al, 2004 ; Li et al, 2008 ; Ayoub et al, 2011 ; Gentry et al, 2015 ) and humans ( Kasner et al, 2002 ; Dippel et al, 2003b ; den Hertog et al, 2009 ). There are also reports of severe hypothermia (T C = 28°C on hospital admission) following acute APAP overdose ( Rollstin and Seifert, 2012 ). Prior to the present work, this potentially hazardous side-effect had not been confirmed in passive, nutritionally controlled participants or conducted in a temperature controlled environmental chamber.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of APAP on non-febrile temperature regulation has been investigated previously in mice ( Ayoub et al, 2004 ; Li et al, 2008 ; Ayoub et al, 2011 ; Gentry et al, 2015 ) and humans ( Kasner et al, 2002 ; Dippel et al, 2003b ; den Hertog et al, 2009 ). There are also reports of severe hypothermia (T C = 28°C on hospital admission) following acute APAP overdose ( Rollstin and Seifert, 2012 ). Prior to the present work, this potentially hazardous side-effect had not been confirmed in passive, nutritionally controlled participants or conducted in a temperature controlled environmental chamber.…”
Section: Discussionmentioning
confidence: 99%
“…15,1719 To date, no large-scale studies have examined differences in clinical presentation or clinical outcomes of APAP combination compounds. 15,16,20 …”
mentioning
confidence: 99%
“…The efficiency in which PGE 2 (via EP 3 receptor activation in the POA) raises T C during fever would make this a useful mechanism for humans to defend their T C in cold environments or environments set beneath the TNZ. This theory is supported by evidence in animal models [21,[35][36][37], and humans [38][39][40][41][42], whereby COX inhibitors (and thus reduced PGE 2 synthesis) have been shown to cause dose dependent T C reductions in the absence of fever or immune response (afebrile). In the following sections, afebrile animal and human studies that have used COX/PGE 2 inhibitors during cold stress, and its effect on T C regulation, will be discussed.…”
Section: Evidence For Afebrile Pge 2 Mediated Thermogenesismentioning
confidence: 89%
“…In that pilot work [42], participants were passively exposed to 20°C wearing only shorts, which is beneath the human TNZ [49,53]. Finally, a recent case report showed that a 37 year old female presented at accident and emergency with a T C of 17°C, 19 h post ingestion of $50 g oral ACT (overdose) [54]. Based on the evidence presented in the current work, it is possible that ACT mediated PGE 2 blockade rendered the patient incapable of normal thermoregulation, an effect which may have been exacerbated if the patient collapsed in an environment beneath the TNZ.…”
Section: Human Modelsmentioning
confidence: 99%